A STUDY OF SUSTAINABLE DEVELOPMENT GOALS (SDG's) PROCESS IN VILLAGES IN WEST LOMBOK DISTRICT - Rakhmawati, Intan; R. Sapto Hendri BS; Baiq Rosyida Dwi Astuti (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2024)
Village governments have received village funding from the central government. Villages are increasingly in the spotlight, because they must be guided by SDG's (Sutainable Development Goals). Based on research by Rakhmawati, et al (2021), the planning and budgeting aspects with 18 aspects of Sustainable Development Goals (SDG's) are considered quite complex, with 247 indicators, in 3 pillars (Economic, Social and Environmental). This research is aimed at examining planning and budgeting documents, as well as the implementation of village finances, whether they are in line with the 2021 SDG data collection. The targeted villages are villages in West Lombok Regency, with different typography, namely land, sea/water, and mountains. Based on the type, this research is descriptive research. As a result, in 2022, the SDG program will not be able to bring uniqueness to the stages of village financial management. This was because the application for data collection and measuring SDG sub-indicators was not yet clear in 2022. As a result, village financial implementation realization data were incompletely filled in by villages. Researchers suggest that there are village financial implementation standards that are designed more clearly by the central government, both by the Ministry of Home Affairs and the Ministry of Villages.